2021
DOI: 10.1007/s11103-021-01181-5
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorylated pathway of serine biosynthesis is crucial for indolic glucosinolate biosynthesis and plant growth promotion conferred by the root endophyte Colletotrichum tofieldiae

Abstract: Key message Phosphoglycerate Dehydrogenase 1 of the phosphorylated pathway of serine biosynthesis, active in heterotrophic plastids, is required for the synthesis of serine to enable plant growth at high rates of indolic glucosinolate biosynthesis. Abstract Plants have evolved effective strategies to defend against various types of pathogens. The synthesis of a multitude of specialized metabolites represents one effective approach to keep plant attackers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Serine plays the main role in response to environmental stresses 54,55 . Transcriptomics and metabolomics results suggested that the key genes of tryptophan biosynthesis were co‐expressed with genes of the phosphorylated pathway of serine biosynthesis (PPSB), and the inhibition of PPSB caused a decrease in indole glucosinolates 56 . Therefore, serine metabolism is crucial for the synthesis of indole glucosinolates in plants.…”
Section: Effects Of Aa Metabolism In Response To Abiotic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Serine plays the main role in response to environmental stresses 54,55 . Transcriptomics and metabolomics results suggested that the key genes of tryptophan biosynthesis were co‐expressed with genes of the phosphorylated pathway of serine biosynthesis (PPSB), and the inhibition of PPSB caused a decrease in indole glucosinolates 56 . Therefore, serine metabolism is crucial for the synthesis of indole glucosinolates in plants.…”
Section: Effects Of Aa Metabolism In Response To Abiotic Stressmentioning
confidence: 99%
“…54,55 Transcriptomics and metabolomics results suggested that the key genes of tryptophan biosynthesis were co-expressed with genes of the phosphorylated pathway of serine biosynthesis (PPSB), and the inhibition of PPSB caused a decrease in indole glucosinolates. 56 Therefore, serine metabolism is crucial for the synthesis of indole glucosinolates in plants. An increase in serine and threonine contents and a decrease in glycine content were found in postharvest grapes, citrus fruits and tomatoes, and exogenous melatonin and methyl jasmonate treatments promoted the accumulation of serine and threonine, thereby maintaining antioxidant ability and delaying the senescence of postharvest citrus and tomatoes.…”
Section: Glycine Serine and Threoninementioning
confidence: 99%
“…An important part of the genes regulated by PHR is known or predicted to mediate biosynthesis of defense-related IG (Castrillo et al, 2017). This fact, together with the need for an intact PEN2-myrosinasedependent IG pathway for the beneficial interaction with C. tofieldiae, points, again, to the relevance of these compounds in regulating Brassicaceae interactions with fungal endophytes (Hiruma et al, 2016;Frerigmann et al, 2020;Zimmermann et al, 2021).…”
Section: How Do Fungal Endophytes Interact With Brassicaceae?mentioning
confidence: 99%